Interspecific rootstock can enhance yield of processing tomatoes (Solanum lycopersicum L.) in organic farming. Issue 3 (2nd July 2020) - Caradonia, Federica; Francia, Enrico; Barbieri, Riccardo; Setti, Leonardo; Hagassou, Djangsou; Ronga, Domenico
ABSTRACT: At present, consumer concern about the impact of food production on the environment is driving increased demand for high quality and healthy tomatoes. However, the yield of processing tomatoes in organic systems are generally lower than that in conventional systems and only a limited number of genotypes suitable for low input or organic systems are available for farmers. The technique of grafting commercial genotypes onto selected rootstocks offers a faster alternative to the classic breeding process. Therefore, in this study, the use of the interspecific rootstock RS01658654 (RT1) was assessed, aiming to improve the marketable yield of processing tomatoes grown in an organic cropping system. The non-commercial processing tomato genotype TC266 was grafted onto the interspecific rootstock RT1 and the plants were then grown under organic conditions. In two growing seasons, morphological, physiological and agronomic performances of grafted processing tomato plants were compared to non-grafted and self-grafted plants. TC226 grafted onto RT1 had a higher number of flowers and leaves compared with the non-grafted and the self-grafted plants. In addition, the marketable yield (significant in 2017 only), the number of fruits and the fruit dry weight were higher for plants grown on the interspecific rootstock RT1, without affecting the quality of the fruit. The results of this study showed that the use of the interspecific rootstock RT1 could provide a good option for improving the production of processing tomatoes in organic farming.